The Appointment of Acting (Contract) Judges and Judicial Independence in Uganda: Understanding Article 142 of the Constitution in Light of its Drafting History - Mujuzi, Jamil Ddamulira (Universitas Islam Negeri Raden Intan Lampung, 2025)
Article 142(1) of the Constitution of Uganda (1995) provides that “The Chief Justice, the Deputy Chief Justice, the Principal Judge, a Justice of the Supreme Court, a Justice of Appeal and a Judge of the High Court shall be appointed by the President acting on the advice of the Judicial Service Commission and with the approval of Parliament.” Article 142(2) provides for the circumstances in which the President may appoint someone “to act” as “a Justice or Judge even though that person has attained the age prescribed for retirement in respect of that office.” Article 147(1)(a) empowers the Judicial Service Commission to advise the President to appoint both permanent and acting judicial officers. In Kabumba and Another v Attorney General (2022), the Constitutional Court held, by majority, that the President does not have the power to appoint acting judges under Article 142(2) unless the appointees are serving or retired judicial officers. In this article, the methodology used by the author is to rely on the drafting history of Article 142 of the Constitution to argue that the President has the power to appoint acting judges or justices and that the appointee does not have to be a serving or retired judge. The author also relies on practice from other Commonwealth countries on the appointment of acting judges to demonstrate that this phenomenon is not unique to Uganda. Practice from other African countries such as Seychelles, Eswatini, Botswana, Sierra Leone, Ghana, Mauritius, South Africa, Tanzania and Namibia shows that acting judges are appointed from either former judges, academics or private legal practitioners. The same approach is followed in many countries outside of Africa such as India, Jamaica, Malta, Marshall Islands, Nauru, Papua New Guinea, Samoa and Tonga. The study is significant because it is the first of its kind to discuss Article 142(2) of the Constitution in detail.